Lo sonoro en la escena transmediática - Vélez, Juan; Maristany, Ana; Sánchez Ferreiro, Alejandra; Pereyra, Marta (2021)
Fil: Vélez, Juan. Universidad Nacional de Córdoba. Escuela de Ciencias de la Información; Argentina.